Relationship between iron-deficiency anemia and heavy metals or parasites in adolescents who consume groundwater - Bustinza-Salas, Daisy Rossy (2021)
Objective: To determine the relationship between iron deficiency anemia and the presence of heavy metals or parasites in adolescents who consume groundwater in Juliaca, Puno. Material and methods: Prospective and analytical study. The concentration of arsenic and aluminium in groundwater was analyzed by spectrophotometry by optical emission in 24 samples, the concentration of arsenic and aluminium in urine by mass spectrophotometry coupled in inductive plasma in 24 samples; presence or absence of Giardia lamblia and Entamoeba histolytica in direct parasitological analyses in 24 groundwater samples; haematoglobin, hematocrit and corpuscular constants tests in 92 adolescent residents of the Taparachi urbanization, during the year 2019. Results: Permissible levels of arsenic were found in groundwater, hemoglobin, hematocrit and corpuscular constants were found within the reference values considered normal in adolescents. However, arsenic levels were found to be above acceptable levels in adolescent urine, these values are found by a type of organic arsenic or adolescents are being tolerant to very low levels of inorganic arsenic being permissible in groundwater. Acceptable levels of aluminum in urine were found in adolescents, while the impermissible values of aluminum in groundwater are for any other external cause. It was shown that there is no presence of Giardia lamblia and Entamoeba histolytica in groundwater. Conclusion: There is no relationship between iron deficiency anemia and groundwater consumption in adolescents.